TRADISI FILSAFAT ILUMINASIONISME DAN PENGARUHNYA TERHADAP KAJIAN FILSAFAT ISLAM - Maulana, Muhammad Iqbal; Arsyi, Syahuri (TAJDID: Jurnal Ilmu Ushuluddin, 2021)
After al-Ghazali attack to the tradition of Islamic philosophy with Tahafutul al-Falasifah, tradition of Islamic philosophy in area of Muslims that decline and stagnation. In Persian world, tradition of Islamic philosophy, have development with new perspective. Tradition of Islamic philosophy in the Persian rise up with Muslim philosopher Suhrawardi by philosophy of illumination with al-Hikmah al-Isyraqiyyah, as an sinthesis to philosophy peripatetic which has long dominated in the tradition of Islamic philosophy studies. This article to the explore development of the tradition and influence Suhrawardi School of illumination to the tradition of Islamic philosophy. Suhrawardi’s school of illumination philosophy has an influence to the next generation, especially in Islamic philosophy in Isfahan, Iraq and in the Islamic world. Pasca serangan al-Ghazali melalui Tahafutul al-Falasifah tradisi kajian filsafat Islam di kalangan umat Islam mengalami kemunduran dan kemandekan. Di Persia tradisi tradisi kajian filsafat Islam justru mengalami perkembangan dengan sudut pandang baru. Tradisi kajian filsafat Islam di Persia memunculkan filosof Muslim bernama Suhrawardi dengan mazhab iluminasi dengan al-Hikmah al-Isyraqiyyah, sebagai sintesis dari filsafat peripatetik yang telah lama mendominasi tradisi kajian filsafat Islam. Artikel ini akan mengulas perkembangan tradisi dan pengaruh mazhab iluminasi Suhrawardi terhadap tradisi kajian filsafat Islam. Mazhab iluminasi Suhrawardi, telah memberikan pengaruh terhadap generasi sesudahnya, terutama dalam kajian filsafat Islam di Isfahan Iraq dan dunia Islam.